Reconstruction of a Bony Bankart Lesion: Best Fit Based on Radius of Curvature. (May 2013) - DeHaan, Alexander; Munch, Jacqueline; Durkan, Michael; Yoo, Jung; Crawford, Dennis
Background: The inferior coracoid process has traditionally been considered to be the gold standard for glenoid augmentation after anteroinferior bone loss. Other autograft sites, and more recently, osteochondral allograft sites, have been described as potential donor sources. Purpose: Potential autograft and osteochondral allograft sites were compared to identify the graft source that would provide the best fit for glenoid augmentation. Study Design: Controlled laboratory study. Methods: Mose circles, a geometric tool found on a standard goniometer, were used to make radius of curvature measurements of 10 anatomic locations in 17 cadaveric specimens. The bony surface of the glenoid, measured from superior to inferior (G-SI) and from anterior to posterior (G-AP), was used as the standard for comparison. Autograft sites were the inferior coracoid, lateral coracoid, and inner table of the iliac crest. Potential osteochondral allograft sites were the radial head, scaphoid fossa of the distal radius (S-DR), lunate fossa of the distal radius (L-DR), medial tibial plateau, and lateral distal tibia. An acceptable match for autograft sites was based on a paired analysis and defined as a radius of curvature within 5 mm of the G-SI or the G-AP of the same cadaveric specimen. Allograft sites were evaluated using an unpaired analysis in which an ideal fit was defined as a radius of curvature of 25 to 30 mm, based on the interquartile range of the G-SI and G-AP. Results: The median (interquartile range) radii of curvature for the G-SI and G-AP were 30 mm (range, 25-30 mm) and 25 mm (range, 25-25 mm), respectively. The inferior coracoid was within 5 mm of the G-SI 59% of the time and the G-AP 94% of the time; no measurements from the lateral coracoid or iliac crest were within the range of the glenoid radius of curvature. Analysis of the allograft sites demonstrated an acceptable fit for 94% of the distal tibia, 68% of the medial tibial plateau, 12% of the S-DR, and 0% of the L-DR and the radial head specimens. Conclusion: An autograft of the inferior coracoid or an osteochondral allograft of the lateral distal tibia provided the best match to re-establish the native radius of curvature of the glenoid. Clinical Relevance: To best re-create the native glenohumeral anatomy, surgeons should consider the use of an autograft of the inferior coracoid or an osteochondral allograft of the lateral distal tibia for the reconstruction of osseous glenoid defects.